Realization of the Use of the Tense Aspects in Oral Communication - Eka Nur Ummu Khasanah; Adi Sutrisno (ITScience (Information Technology and Science), 2022)
After years of learning English, Indonesian prospective workers tend to make many errors in the use of tense aspects in oral communication. The study was aimed at reporting the main factors of the realization of tense aspect usage in oral communication. It has supported the research of Aditya and Chairuddin (2021), that the respondents found difficulties in the use of the correct tense aspects in conversation. The data were collected by interview method using the instruments of twelve questions, each of which used the twelve types of tense aspects, to the thirty students of Kulon Progo Work Training Center. The results demonstrated that they still lacked an understanding of the meaning, usage, and function of 12 types of tense aspects in spoken English. The errors in the equivalence of the time reference between the questions and answers were 82,78% of the dialogues. The first factor they made errors was that respondents tend to do overgeneralizations by using 79% of sentences in Simple Present Tense as the dominant tense aspect. The second factor was that they still defended using the time marking system of L1 in L2. Even though the rough translation of the dialogues in Bahasa could be 93,33 % accepted in Bahasa’s meaning, the original answers in English were not permissible in English grammar. The realization of using the English time-marking system in oral communication is that the respondents tend to make many errors and establish it being their standard language among the communities.